Compound Heterozygote for a Novel Elongated C-Terminal β-Globin Variant (HBB: c.364delG) and Hb E (HBB: c.79G>A) with Heterozygous α-Thalassemia-2. (2nd January 2019) - Nuinoon, Manit; Thipthara, Orapan; Fucharoen, Suthat
Abstract: This study reports the case of 2-year-old Northeastern Thai girl with β-thalassemia (β-thal) disease who has required regular blood transfusions since she was 8 months old. Hemoglobin (Hb) analysis by high performance liquid chromatography (HPLC) separated Hb A2 /E (16.5%), Hb F (22.7%), Hb A (51.8%) and an abnormal peak (Hb X) found at a retention time (RT) of 5.05 min. (C-window) with 2.8%. Multiplex gap-polymerase chain reaction (gap-PCR) revealed heterozygous α-thalassemia-2 (α-thal-2) (–α 3.7 /αα; NG_000006.1: g.34164_37967 del3804). This patient was suspected of having a β-globin chain variant and Hb E ( HBB : c.79G>A) according to the high Hb F level and disease presentations. Surprisingly, Hb Mahasarakham (the geographic origin of the proband), a novel single nucleotide deletion (–G) at the first nucleotide of codon 121 ( HBB : c.364delG), was identified by direct DNA sequencing and secondary confirmation by PCR-restriction fragment length polymorphism (PCR-RFLP). This novel mutation causes a frameshift mutation and added 10 more residues to the β-globin chain that was elongated to 156 amino acids. Molecular basis of this novel mutation in the heterozygous state is required to confirm the mode of inheritance.